Comparison of Huntington’s disease phenotype progression in male and female heterozygous FDNQ175 mice - Li, Si H.; Colson, Tash-Lynn L.; Chen, Jingwei; Abd-Elrahman, Khaled S.; Ferguson, Stephen S. G. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Huntington’s Disease (HD) is an inherited autosomal dominant neurodegenerative disorder that leads to progressive motor and cognitive impairment due to the expansion of a polyglutamine (CAG) repeat in the N-terminal region of the huntingtin (Htt) protein. The creation of HD mouse models represents a critical step in the research for HD treatment. Among the currently available HD mouse models, the zQ175 knock-in mouse line is the first to display robust disease phenotype on a heterozygous background. The newer FDNQ175 mouse model is derived from the zQ175 mouse line and presents a more aggressive phenotype. Moreover, increasing evidence has implicated sex as a contributing factor in the progression of HD symptoms. Here, we compared the progression of HD phenotypes in male and female heterozygous FDNQ175 mice. We found that both male and female heterozygous mice showed deficits in forelimb grip strength and cognition as early as 6 months of age. However, female FDNQ175 mice were less vulnerable to HD-associated decline in limb coordination and movement. Neither male nor female FDNQ175 mice exhibited reduced locomotor activity in the open field or exhibit consistent differences in anxiety at 6–12 months of age. Both male and female FDNQ175 mice exhibited increased numbers of huntingtin aggregates with age and 8-month-old female FDNQ175 mice had significantly more aggregates than their male counterparts. Taken together, our results provide further evidence that sex can influence the progression of HD phenotype in preclinical animal models and must be taken into consideration for future HD research.